EFEKTIVITAS REFORMASI BIROKRASI BERDASARKAN PERWALI NOMOR 39 TAHUN 2023 DI BAGIAN ORGANISASI SEKRETARIAT DAERAH KOTA SURAKARTA - Winagil, Nia; Suhita, Damayanti; Kusumawijayanto, Purbayakti (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2025)
Bureaucratic reform aims to create effective, efficient, and accountable governance. The Surakarta City Government issued Mayor Regulation (Perwali) No. 39 of 2023 to accelerate the implementation of bureaucratic reform at the regional level. However, its implementation still faces challenges, such as lack of coordination between agencies, civil servants’ (ASN) adaptation to new policies, and the effectiveness of evaluation and monitoring mechanisms. If not addressed, these obstacles may hinder the achievement of bureaucratic reform objectives and reduce the quality of public services. Therefore, this study is necessary to evaluate the effectiveness of policy implementation. This study employs a qualitative method with a descriptive approach. Data were collected through direct observation, interviews with ASN in the Organization Division of the Regional Secretariat of Surakarta City, and analysis of policy documents and bureaucratic reform evaluation reports. The effectiveness of this regulation was assessed based on four effectiveness indicators from Tangkilisan (2005): target achievement, adaptability, job satisfaction, and responsibility. The findings indicate that the implementation of Mayor Regulation No. 39 of 2023 has improved bureaucratic reform effectiveness, particularly in achieving reform targets and enhancing digitalization through the Electronic-Based Government System (SPBE). Civil servants have shown a good level of adaptation to policy changes, and a more structured work system has contributed to increased job satisfaction. However, challenges remain in inter-agency coordination and workload management, which hinder the optimization of bureaucratic reform policies. Based on these findings, this study recommends strengthening inter-agency coordination, optimizing data-driven monitoring and evaluation systems, enhancing civil servant competencies in information technology, and reinforcing the BerAKHLAK work culture through an improved reward and punishment system to ensure more effective and sustainable bureaucratic reform. Keywords: Bureaucratic Reform, Effectiveness